Investigating The Lecturers’ Challenges In Implementing Project-Based Learning In Writing Class - Neni Nurkhamidah (Sustainable, 2023)
This is qualitative research that implemented in English Department of Media Nusantara Citra University by involving five lecturers who teach writing classes. The researcher applies interviews to obtain the data. The interview questions are designed semi-structured, and some questions arise during the interview. The data obtained by the researcher are analyzed and coded to find the challenges encountered by lecturers. The finding shows that 5 lecturers involved in this research encountered challenges when they implement PBL. The challenge related to shifting the instruction to facilitating group work, time, creating the project, designing the project, managing group working, managing the project, and assessing the project. To overcome this problem, it is suggested Media Nusantara Citra university conduct seminars or workshops to enrich the lecturers’ knowledge and skill in implementing PBL.